Early Life to Adult Brain Lipidome Dynamic: A Temporospatial Study Investigating Dietary Polar Lipid Supplementation Efficacy - Oliveira, Manuel; Koshibu, Kyoko; Rytz, Andreas; Giuffrida, Francesca; Sultan, Sebastien; Patin, Amaury; Gaudin, Mathieu; Tomezyk, Aurore; Steiner, Pascal; Schneider, Nora (Frontiers in Nutrition, 2022)
The lipid composition of the brain is well-regulated during development, and the specific temporo-spatial distribution of various lipid species is essential for the development of optimal neural functions. Dietary lipids are the main source of brain lipids and thus contribute to the brain lipidome. Human milk is the only source of a dietary lipids for exclusively breast-fed infant. Notably, it contains milk fat globule membrane (MFGM) enriched in polar lipids (PL). While early life is key for early brain development, the interplay between dietary intake of polar lipids and spatial dynamics of lipid distribution during brain development is poorly understood. Here, we carried out an exploratory study to assess the temporal profiling of brain lipidome between postnatal day (PND) 7 and PND 50 by using matrix-assisted laser desorption ionization as a mass spectrometry imaging (MALDI-MSI) in a preclinical model. We also assessed the effect of chronic PL supplementation containing major lipid classes found in the brain (37% phospholipids and 15% sphingomyelin). MALDI-MSI of the spatial and temporal accretion of lipid species during brain development showed that the brain lipidome is changing heterogeneously along time during brain development. In addition, increases in 400+ PL-supplement-dependent lipids increases was observed. PL supplementation had significant spatial and temporal effect on specific fatty esters, glycerophosphocholines, glycerophosphoethanolamines, and phosphosphingolipids. Interestingly, the average levels of these lipids per brain area tended to be constant in various brain structures across the age groups, paralleling the general brain growth. In contrast, other lipids, such as CDP-diacylglycerol, diacylglycerophosphates, phosphocholines, specific ether-phosphoethanolamines, phosphosphingolipids, glycerophosphoinositols, and glycerophosphoserines showed clear age-dependent changes uncoupled from the general brain growth. These results suggest that the dietary PL-supplementation may preferentially provide the building blocks for the general brain growth during development. Our findings add to the understanding of brain-nutrient relations, their temporo-spatial dynamics and potential impact on neurodevelopment.